Novel Perceived Stress and Life Events Precede Flares of Inflammatory Bowel Disease: A Prospective 12-Month Follow-Up Study. (29th October 2018) - Wintjens, Dion S J; de Jong, Marin J; van der Meulen-de Jong, Andrea E; Romberg-Camps, Mariëlle J; Becx, Marco C; Maljaars, Jeroen P; van Bodegraven, Ad A; Mahmmod, Nofel; Markus, Tineke; Haans, Jeoffrey; Masclee, Ad A M; Winkens, Bjorn; et al.
Abstract: Background and Aims: Inflammatory bowel disease [IBD] is characterized by recurrent disease flares. The impact of psychosocial wellbeing on the occurrence of flares is unclear. In this prospective study, we aimed to evaluate the association between patient-reported psychosocial wellbeing and disease flares using continuous monitoring. Methods: Consecutive IBD patients were recruited from the myIBDcoach telemedicine study cohort. Over 12 months, participants reported on disease activity together with anxiety, depression, fatigue, perceived stress and life events every 1–3 months. Flares were defined using a combination of clinical disease activity and additional measurements. Generalized estimating equation models were used to assess associations between psychosocial wellbeing and flares over time. The influences of both the presence of psychosocial symptoms in general as well as novel psychosocial symptoms were analysed. Results: In total, 417 patients were included. Forty-nine patients [11.8%] experienced a flare during the study period. The occurrence of life events in the preceding 3 months was positively associated with flares (odds ratio [OR] = 1.81; 95% confidence interval [CI] = 1.04–3.17), while the presence of anxiety, depression, fatigue and perceived stress in general was not. However, novel perceived stress [OR = 2.92; 95% CI = 1.44–5.90] was associated with flares. Conclusions: The occurrence of life events and novel perceived stress are associated with disease flares in the next 3 months, while the presence of perceived stress in general is not. These findings underline the importance of continuous personalized monitoring of IBD patients and may contribute to the prevention of disease flares.